Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS): A preliminary survey among patients in Switzerland - Rea Tschopp; Rahel S. König; Protazy Rejmer; Daniel H. Paris (Heliyon, 2023)
Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a multi-factorial systemic chronic debilitating disease of poorly understood etiology and limited systematic evidence. The questionnaire and interview-based survey included 169 ME/CFS patients from the Swiss ME/CFS association. The majority of patients were females (72.2%), single (55.7%) and without children (62.5%). Only one third were working (full/part-time). The mean onset of ME/CFS was 31.6 years of age with 15% of patients being symptomatic before their 18th birthday. In this cohort, patients had documented ME/CFS for a mean 13.7 years, whereby half (50.3%) stated their condition was progressively worsening. Triggering events and times of disease onset were recalled by 90% of the participants. An infectious disease was associated with a singular or part of multiple events by 72.9% and 80.6%, respectively. Prior to disease onset, a third of the patients reported respiratory infections; followed by gastro-intestinal infections (15.4%) and tick-borne diseases (16.2%). Viral infections were recalled by 77.8% of the respondents, with Epstein Barr Virus being the most commonly reported agent. Patients self-reported an average number of 13 different symptoms, all described specific triggers of symptoms exacerbation and 82.2% suffered from co-morbidities. This study collated clinically relevant information on ME/CFS patients in Switzerland, highlighting the extent of disease severity, the associated factors negatively affecting daily life activities and work status as well as potential socio-economic impact.